Perancangan PLTS Atap di Gedung Fakultas Teknik Universitas Papua Menggunakan Software PVSyst dan Easysolar: Designing a Rooftop Solar Power Plant at the Faculty of Engineering University of Papua using PVSyst and EasySolar Software - Martinus Kual; Antonius D. Palintin; Pandung Sarungallo (JISTECH: Journal of Information Science and Technology, 2022)
Electrical energy used in Manokwari, West Papua, is still dominated by fossil energy sources. One of the efforts to reduce the use of fossil energy is to utilize potential renewable energy sources in Manokwari. One of these sources is solar energy with irradiation of 4,859 kWh/m²/day. Rooftop PV is one application of the use of solar energy. In this study, the design of the rooftop solar power plant in the Faculty of Engineering, University of Papua was simulated using EasySolar and PVSyst software. With an azimuth angle of 36°, a roof slope of 35°, a roof area of 1,184.94 m², and an installed power of 66 kWp, it takes 220 panels with a capacity of 300 Wp, 2 inverters with a capacity of 33.3 kW. The layout of PV module on the rooftop is simulated using EasySolar software resulting a total of 220 modules on required a roof area of 594 m². In the simulation output using PVsyst software, it is obtained 99.07 MWh per year and the percentage of savings per year is 102.5%.